2018
DOI: 10.1016/j.phrs.2017.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes and cardiac stem cells: Common features and peculiarities

Abstract: Clinical data and basic research indicate that the structural and functional alterations that characterize the evolution of cardiac disease towards heart failure may be, at least in part, reversed. This paradigm shift is due to the accumulation of evidence indicating that, in peculiar settings, cardiomyocytes may be replenished. Moving from the consideration that cardiomyocytes are rapidly withdrawn from the cell cycle after birth, independent laboratories have tested the hypothesis that cardiac resident stem/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 122 publications
0
9
0
Order By: Relevance
“…In the last few years, there have been high expectations that endogenous stromal cardiac mesenchymal cells, originally defined as cardiac progenitor cells (CPCs), were endowed with cardiomyogenic and cardiovascular commitment potential. Indeed, CPCs have been long considered as an appealing source for cardiac regeneration via their in situ reactivation, expansion and differentiation or, alternatively, by means of trans-differentiation of either autologous or allogeneic ones transplanted into the injured myocardium [48][49][50][51][52][53][54][55] Multiple independent investigators have reported several heterogeneous CPC populations according to specific isolation protocols and marker expression patterns [54][55][56][57][58][59][60]. Notably, CPCs and, in particular, epicardium-derived progenitor cells, namely EPDCs, have been suggested to play a pivotal role in modulating the underlying myocardium and directly supporting to coronary vascular smooth muscle cells, cardiac fibroblasts and possibly a small proportion of ventricular cardiomyocytes.…”
Section: Cardiac Regeneration By Rejuvenation: Challenging the Postnamentioning
confidence: 99%
“…In the last few years, there have been high expectations that endogenous stromal cardiac mesenchymal cells, originally defined as cardiac progenitor cells (CPCs), were endowed with cardiomyogenic and cardiovascular commitment potential. Indeed, CPCs have been long considered as an appealing source for cardiac regeneration via their in situ reactivation, expansion and differentiation or, alternatively, by means of trans-differentiation of either autologous or allogeneic ones transplanted into the injured myocardium [48][49][50][51][52][53][54][55] Multiple independent investigators have reported several heterogeneous CPC populations according to specific isolation protocols and marker expression patterns [54][55][56][57][58][59][60]. Notably, CPCs and, in particular, epicardium-derived progenitor cells, namely EPDCs, have been suggested to play a pivotal role in modulating the underlying myocardium and directly supporting to coronary vascular smooth muscle cells, cardiac fibroblasts and possibly a small proportion of ventricular cardiomyocytes.…”
Section: Cardiac Regeneration By Rejuvenation: Challenging the Postnamentioning
confidence: 99%
“…The positive identification of primitive cardiac cells was performed using a few antigenic markers, namely cardiac stem/progenitor cells known to express either c-kit, the stem cell factor receptor, or sca-1 [Beltrami and Madeddu, 2018]. Therefore, the c-kit+ and/or sca-1+ TC-like cells identified by means of light microscopy could also be TC-like cardiac stem/progenitor cells that were not tested for other specific markers, such as Isl-1, or other markers of mesenchymal stem cells.…”
Section: Expression Of Stem/progenitor Markers In Cardiac Tcs: the Vamentioning
confidence: 99%
“…In larger vessels of the myocardium, a sparse layer of pericytes separates the endothelium from the VSMCs and the elastic structures of the vessel ( 66 ). Morphologically they can be distinguished for their thin and elongated cytoplasm, numerous finger-like projections and the rounded nucleus ( 67 , 68 ). A range of surface (PDGFRβ, CD146, CD13 and NG2) or cytoplasmic markers (αSMA, desmin, vimentin, and nestin) are commonly used to identify this specific cell population ( 68 70 ).…”
Section: The Role Of Vascular Smooth Muscle Cells and Pericytesmentioning
confidence: 99%